Administrative measures to overcome problems of providing service SGSSS (2016)
The current situation in the provision of service services general social security health (SGSSS), shown inefficient due to widespread corruption, economic, social and political inequality, the worst is that the provision of health services is located as a business that generates revenue and profits for some individuals.This problem is due to bad management decisions that have been implemented in the system. To understand it is necessary to take a tour of the history of the system and the reforms that have suffered the same. We must remember then that there historically 3 periods in which you can see the most important changes has presented the service of health. The first begins with the promulgation of the Constitution of 1886 until mid-1950 and which prevailed in what can be termed as the "hygienist model.The health system has spent several years in crisis. Repeated attempts to put order have been unsuccessful. Clearly the system has many insurers do not deserve that name. Few are protecting their members with ethics and responsibility. But they do not learn.The solutions that have been put on the table seem to offer a leap, with incalculable consequences for the health protection of Colombian families. Independent physicians and hospitals must reflect on the implications of centralized public systems, which all countries of the world have departed unsustainable, bad payers and rationing of services to the population.We can not deny that the Congress has sought to redefine the SGSSS by law; establishing principles of the system, within the framework from which health benefits are regulated, operation, management and administration of the provision of services, the unified management of health resources through the creation of a financial management unit But nevertheless; the service continues to generate discontent among the population and the numbers of dead are growing; the huge queues to acquire or obtain an appointment to be seen by a doctor are the main complaints of users.